Responses to the COVID-19 Pandemic in Chinese Higher Education: A Reflection upon International Student Support - Zhang, Yun; Zhu, Yining (Journal of International Students, 2022)
The COVID-19 pandemic has posed overwhelming challenges to higher education around the world. It has significantly affected the internationalization of Chinese higher education. The University of Nottingham Ningbo China (UNNC), as the first Sino-foreign cooperative university in the country, has witnessed a growing number of international students from 70 countries and regions in recent years. In response to the pandemic, the University has developed a series of strategies to support international students on campus and overseas. Through a case study approach, we explore the significant problems encountered by international students during this challenging time and the services and support provided by the University to help them cope with such challenges. It proceeds to reflect upon effective measures implemented so far and lessons learned. We aim to provide useful experience and advice for higher education professionals responding to issues pertaining to international student management and services in times of crisis.